Effect of age-related musculoskeletal conditions on senior golfer physical capacity, golf performance ability and playing characteristics - Joyce, C.; Farringdon, F.; Bycroft, J.; Anthony, S.; Conlon, J. (International Journal of Golf Science, 2022)
This study investigated previously un-reported differences in a holistic assessment of senior golfers. Fifteen `healthy` seniors (M 66.8 ± 10.0, F 71.6 ± 4.4 years) with no age-related musculoskeletal conditions (ARMC) were compared to 37 seniors with an ARMC (M 71.8 ± 7.3, F 67.6 ± 6.4 years). Golf playing characteristics (e.g. lessons, practise), anthropometric, physical capacity, and golf performance ability testing was undertaken. The healthy group reported a greater frequency of walking the course, less use of professional coaching (lessons), and focused practise more on long game. Superior physical capacity performance in the healthy group for significantly increased flexibility, quicker timed up and go, increased sit to stand score, and longer trunk extension time was reported. Healthy males also out-performed condition males for the majority of golf performance ability assessments. Important links and a greater understanding of these factors have helped to further explain golf `health` within this cohort.